Hospice care for children - Armstrong-Dailey, Ann.; Zarbock, Sarah F. (New York ; Oxford : Oxford University Press, 2009)
This text, the first edition of which won the 1993 Pediatric Nursing Book of the Year Award, provides an authoritative source for the many people involved in caring for dying children. The practical topics can be put to immediate use.
Previous ed.: 2001.
Errata slip inserted.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Terminally ill children -- Care; Hospice care